2014
DOI: 10.14419/ijans.v3i1.1931
|View full text |Cite
|
Sign up to set email alerts
|

Health promoting lifestyles of Jordanian university students

Abstract: Background: Health-promoting lifestyles of university students are strongly related to their current and subsequent health status. Low rates of health-promoting lifestyles among university students are still reported in literature. However, few studies in Jordan have examined health-promoting behaviors among university students. Objectives: This study was aimed to assess health-promoting lifestyles among university students and to examine relationship between the university student's characteristics and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 18 publications
7
28
1
2
Order By: Relevance
“…Two different studies (Panebianco-Warrens, Fletcher & Kreutz 2014; Kreutz 2008) conducted among music students revealed that female students displayed health-promoting behavior as well as significantly higher score for NB as compared to the male students. In contrast to the current findings, the studies conducted by Alkhawaldeh (2013) and Vançelik et al (2007) revealed that the average score of NB was higher in males than the females; it was not significant in first one, while it was significant in the second (Vançelik et al 2007;Alkhawaldeh 2014). Some previous studies did not present significant differences in HPLP-II scores between females and males (Wei et al 2011;Mirghafourvand et al 2014;Nacar et al 2014).…”
Section: Discussioncontrasting
confidence: 95%
“…Two different studies (Panebianco-Warrens, Fletcher & Kreutz 2014; Kreutz 2008) conducted among music students revealed that female students displayed health-promoting behavior as well as significantly higher score for NB as compared to the male students. In contrast to the current findings, the studies conducted by Alkhawaldeh (2013) and Vançelik et al (2007) revealed that the average score of NB was higher in males than the females; it was not significant in first one, while it was significant in the second (Vançelik et al 2007;Alkhawaldeh 2014). Some previous studies did not present significant differences in HPLP-II scores between females and males (Wei et al 2011;Mirghafourvand et al 2014;Nacar et al 2014).…”
Section: Discussioncontrasting
confidence: 95%
“…These results are also similar with the findings of the other studies. [ 14 18 19 20 21 ] Interpersonal relationships defined as “Seeking support” and intimacy from friends and family, participation in support agency and voluntary activities, participation in educational programs, seeking professional counseling when needed. [ 15 ] In our study, the majority of students sought support and participated in some sort of support activities.…”
Section: Discussionmentioning
confidence: 99%
“…The significant result in healthy dietary practices and physical activity among 24 years and older may be related to their personal health responsibility as older adults. Study showed that health responsibility and control of stress had a better link with physical activity and proper nutrition which means, when an older adult college student have a higher health responsibility, the more evident is the practice of a healthy lifestyle (Al-Khawaldeh, 2014). Therefore, health promotion activities may be done at the student's level which can be done better by these older college students in their own dormitories as health mentors.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent study showed that health responsibility and control of stress had a better link with physical activity and proper nutrition which means, when an older adult college student have a higher health responsibility, the more evident is the practice of a healthy lifestyle (Al-Khawaldeh, 2014). This factor may provide a clear message that age could be a link to a better practice of healthy lifestyle, thus the need for further research study.…”
Section: Literature Reviewmentioning
confidence: 99%